Malnutrition as a risk factor for the development of pressure ulcers - Serpa,Letícia Faria (2008)
Malnutrition - as a fundamental aspect both in genesis as in healing of pressure ulcers - is the object of this update paper. Countless studies point out that malnutrition, immune function alterations, hypoalbuminemia, low hemoglobin levels, as well as low diet intake, as responsible for an increase in the risk of developing these lesions. Therefore, it is essential to include the assessment of the nutrition status - monitoring of the calorie-protein intake and the difficulties to use the nutrients - in the prevention and treatment protocols of this type of chronic wound.